Gambaran Pengetahuan Suami tentang Kontrasepsi dengan Metode Operasi Pria (MOP): An Overview of Husband's Knowledge about Contraception with Male Surgical Methods - Angga Arsesiana; Rena Oki Alestari; Anisa Sri Susanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: The Male Operation Method is a method of minor operative contraception that is safe for men, simple and very effective, requires a relatively short operation time, and does not require general anesthesia. However, the use of MOP is still shallow. The lack of progress in male family planning participation with MOP is caused, among other things, by the lack of knowledge, information, awareness, socialization, and facilities for male family planning services. This is because counseling about contraceptives to the public, especially men, is very lacking. The purpose of the study: To describe the husband's knowledge level about the Male Operation Method (MOP). Methods: The research method used in this research is descriptive research using the literature review or literature review method. A total of three journals were reviewed. Results: The results showed that the level of good knowledge was 73 respondents (41.71%), 37 respondents (21.14%) had sufficient knowledge, and 65 respondents (37.14%) lacked knowledge. Conclusion: From the results of the analysis and discussion, the researcher concluded that the husband's knowledge about contraception with the Male Operation Method (MOP) was good; this was influenced by the education level of the respondents, most of whom were high school.